Organoleptic Test Patisserie Product Based on Consumer Preference. (March 2017) - Ana, A; Subekti, S; Hamidah, S; Komariah, K
Abstract: The main objective of this research was to produce innovative patisserie product based on consumers' preferences through organoleptic test. This research was conducted in several stages, namely: preparation phase, organoleptic test phase, and nutritional analysis. The making of patisserie product was done by considering the Segmentation of Consumer Behavior (Behavioristic Segmentation). Preparation phase was the making of product formulation. The determination of selected formula was based on experiment and organoleptic test i.e. hedonic quality test using semi-trained panelists. The next stage was to conduct organoleptic analysis i.e. hedonic quality organoleptic test to the flavor, serving and packaging of the patisserie product. The last step was to analyze the nutrition of the product. This research was an experimental research conducted at the Culinary Arts Laboratory, involving 14 panelists. In this study we used some instruments that was required to collect the research data. The result of this research was the finding of the patisserie product formula i.e. innovative product Cream Puff Nori, Spinach and Salmon. Based on the approach which we used i.e. the organoleptic test, we got result that at the final stage of organoleptic test, Choux paste product was rated as follows: 46.2% of the panelists stated that it was very delicious and 46.2% stated that the flavor of choux paste both content and skin was delicious, and only 7.7% stated that the flavor of choux paste was less delicious. As for the appearance, 38.5% of the panelists stated that the choux paste had a very good appearance and 53.8% stated it had good appearance. Only 7.7% stated that it had less good appearance. Thus the appearance of choux paste was considered better. The packaging was considered very attractive by 30.8% of the panelists and was considered attractive by 46.2% of the panelists. While 23% of the panelists considered the packaging less attractive. Nutritional value of one recipe formula contained energy 2064.8 Kal, 124.13 g protein, 57.13 g of fat and 198.5 g carbohydrate (32 pieces of choux paste).